Chemoselective Claisen–Schmidt bis-substitutional condensation catalyzed by an alkoxy-bridged dinuclear Ti(IV) cluster. Issue 12 (24th March 2016) - Wu, Yufei; Hou, Jie; Liu, Yuliang; Zhang, Mingfu; Tung, Chen-Ho; Wang, Yifeng
Abstract: The highly efficient and chemoselective α, α′-bis-substitution of alkanones is important in organic synthesis. Herein, a dimeric titanium cluster, Ti2 Cl2 (OPr i )6 ·2HOPr i (Ti 2 ), is used in the Claisen–Schmidt condensation reaction, for the selectively activation of symmetrical ketones containing α, α′-methylene groups and production of α, α′-bis-substituted alkanones in high efficiency and chemoselectivity. The high efficiency and chemoselectivity can be extended to a variety of typical alkanones and aromatic aldehydes. Both of the oxo-bridged dimeric motif ofTi 2 and the ionic Ti–Cl bond are responsible for the high efficiency and chemoselectivity. Graphical abstract: